Pengaruh Keterbukaan Komunikasi Pimpinan Perusahaan Dalam Membentuk Peningkatan Dan Kenyamanan Kinerja Karyawan Di PT .Global Sinergi Kartu - Ulfa Maslakhatul Khasanah; Amin Sadiqin (CV ODIS, 2021)
Open communication is a part of the science of business ethics, a business science that is believed to provide benefits not only to companies or to people who run business, but also to employees, the general public, and the natural environment. Open communication becomes a principle thing in running a company in which there are many deserving people. Open communication becomes a principal thing in running a company in which there are many diverse people. Open communication will make people trust each other. Then, open communication will become effective communication. In fact, effective delivery of information will smoothen the workflow of a company so that the company can get maximum results. PT. Global Sinergi Kartu is one of the companies that implement this rule. Employees of the company stated that they tend to like the openness in communication applied by their leaders. The employees feel to be given the freedom to express their opinion and to get clear information. By conducting in-depth interviews to obtain data, this qualitative research shows the result that the application of the principle of information disclosure has a real positive impact on the performance of employees.